The features of the content of bilingual education in secondary schools of the USA (Pedagogy of Higher and Secondary Education, 2013)
Zaitseva N. G. The features of the content of bilingual education in secondary schools of the USA.The article deals with the review of the content of secondary bilingual education in the USA. On the basis of the analysis of the content of bilingual education in the USA secondary schools its most important components and the specifics of pupils’ polycultural development were identified.
Keywords: bilingual education; content of bilingual education; multilingual development; multicultural development; acculturation